Prototype Design Of Geophone Using Piezoelectric Sensor Based On Arduino Uno - Marlina Susanti; Arisalwadi, Meidi; Menasita Mayantasari; Rahmania, Rahmania; Febrian Dedi Sastrawan (Journal of Multidisciplinary Science, 2022)
This study designed a geophone prototype using a piezoelectric sensor based on Arduino Uno. This research aims to create an alternative tool from the geophone that can measure vibrations on the ground. To find out if the geophone sensor that has been designed can work well, namely by knowing how far away the sensor can receive a given vibration source. Geophone design made using a piezoelectric sensor based on Arduino Uno R3. The components used to make the prototype will be connected to the Arduino, with the output as a byte value converted into a voltage. These results were obtained from testing by taking data using a vibration source, namely a dropped load. The testing process is carried out by dropping the vibration source from a height of 55 cm with variations in the distance as far as 20 cm, 30 cm, 50 cm and 60 cm. From the experiments carried out, the prototype made can function to read data from the dropped source. The farther the vibration source is dropped, the smaller the voltage generated. The results obtained from this study are the design of a geophone prototype made on a laboratory scale.